Comparative clinical evaluation of olive oil and coconut oil rinse on plaque levels in gingivitis patients -A Randomized clinical trial - Pratha, Patel; Deshpande, Neeraj (Journal of Orofacial Research, 2020)
Background: In alternative medicine, oil pulling is a procedure that involves swishing oil in the mouth for oral and systemic health benefits. Oil pulling has been proven effective in preventing decay, oral malodor, bleeding gums, dryness of the throat, and cracked lips along with the strengthening of gums and the jaw. Objective: To compare and evaluate the effects of oil pulling with olive oil and coconut oil on gingivitis and plaque score. Methods: A total of 34 selected participants were randomly allocated by lottery method into two groups (Group A- coconut oil; Group B- olive oil) having 17 participants each. After brushing the teeth, participants were asked to rinse with 10 ml of oil till it becomes milky white and then spit out once daily for a period of 30 days. Plaque index (Silness J. and Loe H. 1964) and Gingival Index (Loe H. and Silness J. 1963) were recorded at baseline, at 7, 15, and 30 days. Results: The mean plaque score of Group-A and Group B at baseline was 1.518±0.1629 and 1.535±0.1656 respectively, which significantly reduced after 30 days (Group A- 0.876± 0.1091; Group B- 1.171± 0.0686 p<0.001). The mean gingival score of Group-A and Group B at baseline was 1.571± 0.1649and 1.618±0.1380respectively, which significantly reduced after 30 days (Group A-0.882±0.1286-; Group B- 1.147±0.0514 p<0.001). Conclusion: Although, both coconut oil and olive oil groups showed an effective reduction in values of plaque scores and gingival scores, coconut oil showed a significant decrease in plaque and gingival scores in comparison to olive oil in patients with mild to moderates gingivitis.